1992
DOI: 10.1177/000456329202900224
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyperphosphataemia in Multiple Myeloma

Abstract: We read the article by Hawkins! with great interest and would like to report our findings on the subject.Serum phosphate concentrations were measured in 41 patients who have multiple myeloma with identified serum paraproteins by four methods, the first three methods being performed on a Cobas Mira analyser. (1) Direct single step method using ammonium heptamolybdate in sulphuric acid (absorbance: 340 nm); (2) a modification of the molybdate method with the addition of albumin and formate-(absorbance: 340 nm); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Pseudohyperphosphatemia in the presence of serum paraproteins has been documented on a number of occasions since the introduction of direct methods for the estimation of phosphate. Lai, McClure and Cornell (1992) found that not all paraproteins caused this problem, although the phenomenon is certainly more common than previously realized. The paucity of previous reports may in part reflect the scant attention clinicians routinely pay to phosphate measurements (Larner, 1992, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Pseudohyperphosphatemia in the presence of serum paraproteins has been documented on a number of occasions since the introduction of direct methods for the estimation of phosphate. Lai, McClure and Cornell (1992) found that not all paraproteins caused this problem, although the phenomenon is certainly more common than previously realized. The paucity of previous reports may in part reflect the scant attention clinicians routinely pay to phosphate measurements (Larner, 1992, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…The paucity of previous reports of spurious hyperphosphataemia suggests either that serum globulins do not interfere with phosphate determinations in general (hence the rare association of hyperglobulinaemia with pseudohyperphosphataemia) or that interference is common but of sufficiently minor degree to escape clinical detection in most instances. Lai et al , using a direct acid/moiybdate method, found previously unrecognised spuriously high phosphate concentrations in 11 of 41 patients with multiple myeloma, 14 demonstrating that the phenomenon is probably not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…The precise physicochemical mechanisms by which certain proteins interfere with the phosphomolybdate assay remain to be fully elucidated. As colorimetric and spectrophotometric methods are based on light absorbance, turbidity of the reaction mixture due to precipitation of protein may be relevant 5 , 9 , 10 , 11 , 13 , 14 . By analogy, 11 the increased light absorbance of lipaemic sera is known to interfere with colorimetric assays for chloride 15 and phosphate 5 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having read with interest the recent contributions from Dr Hawkins' and Dr Lai and colleagues/ concerning pseudohyperphosphataernia in multiple 2 find that not all paraproteins cause this problem, although the phenomenon is certainly commoner than previously realized; the paucity of previous reports may in part reflect the little attention clinicians routinely pay to phosphate measurements. 10 The important clinical message to emerge from these studies is that unexplained and persistent hyperphosphataemia should prompt the search for a monoclonal protein prior to potentially inappropriate treatment with phosphate binding agents.…”
Section: Pseudohyperphosphataemia In Multiple Myelomamentioning
confidence: 97%